Adaptive leadership in clinical encounters with women living with HIV - Schenita D. Randolph; Ragan Johnson; Kara McGee; Adaora A. Adimora; Catalina Ramirez; Donald E. Bailey; Lauren Holt; Amie Koch; Jacquelyn M. McMillian-Bohler; Tiarney Ritchwood; Michael V. Relf (BMC, 2022)
Abstract Background Women living with HIV (WLWH) report low engagement in health care, missed office visits, and less engagement in the clinical encounter. Strengthening the clinical encounter for WLWH may improve health outcomes and quality of life. The Adaptive Leadership Framework for Chronic Illness offers specific adaptive leadership strategies for providers to improve patient-provider interactions. The purpose of this study was to examine adaptive leadership behaviors that contribute to the development of effective patient-provider communication from the perspectives of WLWH. Methods The descriptive, cross-sectional and qualitative study conducted interviews with 22 WLWH to assess perceptions of the clinical encounter related to HIV-related stigma, engagement in care, medical distrust, and experiences with discrimination and quality of life. Members of the study team using a set of a priori codes analyzed data using NVivo 12.0. Results Participants described two primary themes and subthemes of each for adaptive leadership behaviors. The primary theme for adaptive leadership of providers was "my provider cares about me"; subthemes were communication, trust building takes time, and supportive providers are trusted. The primary theme for adaptive leadership of WLWH themselves was "I care about me; subthemes were self-advocacy and self-empowerment. Conclusions Providers can use adaptive leadership behaviors during clinical encounters to support WLWH, improve patient-provider communication, enhance trust, and improve patient outcomes.